Analysis of Hydrogeochemical Characteristics and Origins of Chromium Contamination in Groundwater at a Site in Xinxiang City, Henan Province - Wenfang Chen; Yaobin Zhang; Weiwei Shi; Yali Cui; Qiulan Zhang; Yakun Shi; Zexin Liang (Applied Sciences, 2021)
Hexavalent chromium contamination in groundwater has become a very serious and challenging problem. Identification of the groundwater chemical characteristics of the sites and their control mechanisms for remediation of pollutants is a significant challenge. In this study, a contaminated site in Xinxiang City, Henan Province, was investigated and 92 groundwater samples were collected from the site. Furthermore, the hydrogeochemical characteristics and the distribution patterns of components in the groundwater were analyzed by a combination of multivariate statistical analysis, Piper diagram, Gibbs diagram, ions ratio and hydrogeochemical simulation. The results showed that the HCO3-Cl-Mg-Ca type, SO4-HCO3-Na type, and HCO3-Mg-Ca-Na type characterize the hydrogeochemical composition of shallow groundwater and HCO3-Cl-Mg-Ca type, HCO3-Na-Mg type, and HCO3-SO4-Mg-Na-Ca type characterize the hydrogeochemical composition of deep groundwater. Ion ratios and saturation index indicated that the groundwater hydrogeochemical characteristics of the study area are mainly controlled by water–rock action and evaporative crystallization. The dissolution of halite, gypsum and anhydrite, the precipitation of aragonite, calcite and dolomite, and the precipitation of trivalent chromium minerals other than CrCl3 and the dissolution of hexavalent chromium minerals occurred in groundwater at the site. The minimum value of pH in groundwater at the site is 7.55 and the maximum value is 9.26. The influence of pH on the fugacity state of minerals was further investigated. It was concluded that the saturation index of dolomite, calcite, aragonite and MgCr2O4 increases with the increase of pH, indicating that these minerals are more prone to precipitation, and the saturation index of Na2Cr2O7, K2Cr2O7 and CrCl3 decreases with the increase of pH, implying that Na2Cr2O7, K2Cr2O7 and CrCl3 are more prone to dissolution. The saturation index of the remaining minerals is less affected by pH changes. The study can provide a scientific basis for groundwater remediation.